2016
DOI: 10.1073/pnas.1602811113
|View full text |Cite
|
Sign up to set email alerts
|

Superresolved multiphoton microscopy with spatial frequency-modulated imaging

Abstract: Superresolved far-field microscopy has emerged as a powerful tool for investigating the structure of objects with resolution well below the diffraction limit of light. Nearly all superresolution imaging techniques reported to date rely on real energy states of fluorescent molecules to circumvent the diffraction limit, preventing superresolved imaging with contrast mechanisms that occur via virtual energy states, including harmonic generation (HG). We report a superresolution technique based on spatial frequenc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
64
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(64 citation statements)
references
References 43 publications
0
64
0
Order By: Relevance
“…Moving forward, we will disregard this component of the signal since it does not contribute to image formation. We note, however, that the DC intensity does contribute to the overall noise measured in the total signal, S t , and thus contributes to the SNR of the recovered image [15]. …”
Section: Single-pixel Imaging With Spatiotemporally Structured Lightmentioning
confidence: 99%
See 1 more Smart Citation
“…Moving forward, we will disregard this component of the signal since it does not contribute to image formation. We note, however, that the DC intensity does contribute to the overall noise measured in the total signal, S t , and thus contributes to the SNR of the recovered image [15]. …”
Section: Single-pixel Imaging With Spatiotemporally Structured Lightmentioning
confidence: 99%
“…Instead, an SSB is isolated by a time-dependent phase shift imparted to the illumination intensity that manifests as a carrier frequency in the temporal domain. This carrier frequency permits one to isolate all three components of the measured signal—St(0),St(1), and St(1) —with straightforward Fourier signal processing methods [1315,23]. …”
Section: Single-pixel Imaging With Spatiotemporally Structured Lightmentioning
confidence: 99%
“…Tests will entail adding a fluorescing Ca 2+ indicator to the flow solution and conducting laser imaging during flow through experiments to capture Ca 2+ release during dissolution. SPIFI has been used with TPEF and with second-harmonic generation (SHG) to image inorganic and biological samples [6,7]. However, this would be the first time in-situ geochemical dissolution has been captured with SPIFI.…”
mentioning
confidence: 99%
“…In this way, the spatial location is encoded by the Recently, it was demonstrated that using the SPIFI microscope it is possible to obtain images in superresolution (sub-diffraction-limit). 18 When the laser beam passes through the time-dependent spatial modulation pattern, produced by the spinning disk rotation (or, as in our case, by the SLM modulation), the line focus is diffracted into several beams with varying propagation angles, θ j , where j corresponds to the diffracted order, Fig. 7.2.…”
Section: Spatial Frequency-modulated Imaging -Spifimentioning
confidence: 91%
“…81 Recently, SPIFI has been shown to have the added benefit of superresolved multimodal imaging. 18 Multiphoton SPIFI provides spatial resolution up to 2β below the diffraction limit, where β is the highest power of the nonlinear irradiance response, for instance, β = 4 for SHG and β = 6 for THG. Michael we improved the microscope's design and took third-harmonic images for the first time using a SPIFI setup.…”
Section: Introductionmentioning
confidence: 99%